My Professor is asking us to solve the following differential equation and initial value problem but does not provide any further instructions. Could someone please help me get started?

1.) $D^3(D+5)(D+3)^2(D^2+16)y = 0$


2.)$2x e^y \mathrm{d}x+(x^2e^y+y \cos y)\mathrm{d}y = 0$

  • $\begingroup$ Multiplication, i'll make the change $\endgroup$ – user100707 Dec 11 '13 at 16:07
  • $\begingroup$ Hint for $2.$, it is an Exact Equation. The first one could not me more straightforward. $\endgroup$ – Amzoti Dec 11 '13 at 16:08
  • $\begingroup$ Is solving a differential equation the same as providing a general solution for it? $\endgroup$ – user100707 Dec 11 '13 at 16:09
  • $\begingroup$ Please, stop writing latex with only $\$^y\$$, the dollar notation is meant to be used for a whole equation. Well, sorry, it's not especially after you, but it's a bad habit that seems to spread on MSE. $\endgroup$ – Jean-Claude Arbaut Dec 11 '13 at 16:10
  • $\begingroup$ @user100707: Yes, you can solve these, but do not have initial conditions, thus will have unknown constants floating about. $\endgroup$ – Amzoti Dec 11 '13 at 16:11

According to The Annihilator Method, we have the following points for 1. :

  • When we have the term $D^3$ in the ODE so the terms $$c_1+c_2x+c_3x^2$$ will appear in $y(x)$.

  • When we have the term $D+5$ in the ODE so the terms $$c_4\exp(-5x)$$ will appear in $y(x)$.

  • When we have the term $(D+3)^2$ in the ODE so the terms $$c_5\exp(-3x)+c_6x\exp(-3x)$$ will appear in $y(x)$.

  • When we have the term $D^2+16$ in the ODE so the terms $$c_7\sin(4x)+c_8\cos(4x)$$ will appear in $y(x)$.


1) If we set $$ P_1=D^3,\quad P_2=D+5,\quad P_3=(D+3)^2,\quad P_4=D^2+16, $$ then $P_iP_j=P_jP_i$ for every $i,j$. Therefore, the general solution $y$ of $$ D^3(D+5)(D+3)^2(D^2+16)y=P_1P_2P_3P_4y=0 $$ is given by $$ y=\mu_1\phi_1+\mu_2\phi_2+\mu_3\phi_3+\mu_4\phi_4, $$ where $\mu_1,\mu_2,\mu_3$ and $\mu_4$ are real constants and $$ P_1\phi_1=0,\quad P_2\phi_2=0,\quad P_3\phi_3=0,\quad P_4\phi_4=0. $$ It is obvious that \begin{eqnarray} \phi_1(x)&=&a_0+a_1x+a_1x^2,\quad \phi_2(x)=be^{-5x},\\ \phi_3(x)&=&(c_0+c_1x)e^{-3x},\quad \phi_4(x)=d_1\cos4x+d_2\sin4x. \end{eqnarray} Hence $$ y=C_0+C_1x+C_2x^2+C_3e^{-3x}+C_4e^{-5x}+C_5\cos4x+C_6\sin4x. $$ 2) Since $$ \frac{\partial}{\partial x}(x^2e^y+y\cos y)=2xe^y=\frac{\partial}{\partial y}(2xe^y), $$ it follows that there exists a function $(x,y) \mapsto f(x,y)$ such that $$ \frac{\partial f}{\partial x}(x,y)=2xe^y,\quad \frac{\partial f}{\partial y}(x,y)=x^2e^y+y\cos y. $$ From the identity $$ \frac{\partial f}{\partial x}(x,y)=2xe^y $$ we deduce that $$ f(x,y)=x^2e^y+g(y). $$ Since $$ \frac{\partial f}{\partial y}(x,y)=x^2e^y+g'(y)=x^2e^y+y\cos y, $$ it follows that $$ g'(y)=y\cos y. $$ Therefore $$ g(y)=\int y\cos y\,dy=\int y(\sin y)'\,dy=y\sin y-\int\sin y\,dy=y\sin y+\cos y+C. $$ Since $$ 2xe^ydx+(x^2e^y+y\cos y)dy=0 \iff df(x,y)=0 \iff f(x,y)=C', $$ where $C'$ is a real constant. It follows that the general solution of $$ 2xe^ydx+(x^2e^y+y\cos ydy)=0 $$ is the family of curves given by $$ x^2e^y+y\sin y+\cos y=c, $$ where $c$ is real constant.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.